Indo-cyanine green administration to identify loss of lymph after axillary lymph node dissection - Roman, Mirela Mariana; Delrue, Pauline; Karler, Clarence; Del Marmol, Véronique; Bourgeois, Pierre (Frontiers in Oncology, 2023)
Background Near infrared fluorescence imaging with Indocyanine Green (ICG) is now used for the imaging of lymph nodes and lymphatic vessels. In this work, we investigated the impact of its pre-operative and peri-operative administration on our ability to detect axillary lymphatic loss after breast cancer surgery. Methods One subcutaneous injection of ICG was administered in the ipsilateral hand of 109 women who were scheduled to have either a mastectomy with total axillary lymph node dissection (CALND) or a lumpectomy with selective lymphadenectomy (SLN) the day before (n = 53) or the same day of surgery (n = 56). The lymph leakages were assessed by means of the application of a compress in the operated armpit and by the presence or absence of fluorescence on it, as well as in the post-operative axillary drains. Results The compress was fluorescent in 28% of SLN patients and 71% of CALND patients. The liquids in the axillary drains were also fluorescent in 71% of patients with CALND. No statistical significance was observed between the ICG injection groups. The association between compressive fluorescent and the presence of fluorescence in the axillary drains is significant in the pre-operative subgroup and in the whole group. Conclusion Our research demonstrates that lymphatic leaks aid in the development of seromas and calls into question the effectiveness of the ligatures and/or cauterizations used during surgery. A prospective, multicentric, randomized trial should be conducted to verify the efficacy of this approach.